Creating added-value filet product from rainbow trout (Oncorhynchus mykiss) by salting and smoking method: physicochemical and textural attributes - Cheng, Yu-Tsung; Huang, Ping-Hsiu; Lu, Wen-Chien; Chu, Sheng-Che; Wang, Pei-Ming; Ko, Wen-Chien; Li, Po-Hsien (Frontiers in Sustainable Food Systems, 2023)
In this study, we investigated rainbow trout (Oncorhynchus mykiss) fish fillets salted in a 5% salt solution for 2 days and then smoked at 65°C for 4 h under different storage conditions. As results, the higher rate of salt penetration and water loss in the resolved rigor mortis group was associated with tenderization of the meat compared to the rigor mortis group. The appearance, flavor, chewiness, and overall acceptability of the smoked fish fillets increased and decreased during the smoking process, which correlated with heated shrinkage and thermal-induced tissue destruction. Nevertheless, according to the results of a consumer-type evaluation, the product characteristics of the fish fillets from the resolution of rigor mortis group were consistent with those of the rigor mortis group, except for a weaker aroma. Thus, these results explain the relationship between frozen stored fish and the quality of processed products. The economic concept of regulating and distributing scheduling production between raw materials and finished products in the food industry conveys promising findings that will contribute to developing sustainable food processing systems.